Experiences in the training of specialist family and community nurses: a qualitative study - Sánchez-Muñoz, Francisca; Fernández-Medina, Isabel María; Granero-Molina, José; Suazo-Galdames, Iván Claudio; Nunez-Nagy, Susana; Ventura-Miranda, María Isabel; Ruíz-Fernández, María Dolores (Frontiers in Public Health, 2023)
Introduction: The specialist Family and Community Nurse Practitioner (FCNP) is a professional who, after a period of training, is qualified to be part of multidisciplinary teams in primary care. The aim of this study was to describe and understand the experiences of nurses during their training process in the specialty of Family and Community Nursing in Spain. Methods: A descriptive qualitative study was carried out. Participants were recruited by means of convenience sampling from January to April 2022. Sixteen specialist nurses in Family and Community Nursing from different autonomous communities in Spain participated in the study. Twelve individual interviews and one focus group were conducted. Data were analyzed following a thematic analysis method in ATLAS.ti 9. Results: The results showed two themes and six subthemes: 1) Residency period, more than a training: a) Training during the residency period; b) Specializing through a constant struggle; c) Moderate optimism about the future of the specialty; and 2) A journey from illusion to disappointment: a) Beginning of the residency: feeling special; b) During the residency: between satisfaction and misunderstanding; c) At the end of the residency: power and frustration. Conclusions: The residency period is important in the training and acquisition of competencies for the Family and Community Nurse Practitioner. Improvements are needed to ensure quality training during residency and to help give visibility to the specialty.